The Ideal Convergence of Strongly of Γ2 in p-Metric Spaces Defined by Modulus - N. Subramanian; K. Balasubramanian; K. Chandrasekhara Rao (Abstract and Applied Analysis)
The aim of this paper is to introduce and study a new concept of the Γ2 space via ideal convergence defined by modulus and also some topological properties of the resulting sequence spaces were examined.